Influence of Coulombic Efficiency in Air-Cathode Microbial Fuel Cell by Temperature and Baffle-microfiltration Membrane Barrier - Li, Chao; Zhang, Libin; Xu, Ming; Ding, Lili; Xu, Ke; Geng, Jinju; Ren, Hongqiang (Asian Journal of Chemistry, 2013)
Coulombic efficiency is an important measurement of energy recovery, which is very low in the air-cathode microbial fuel cell. Temperature variation and baffle-microfiltration membrane barrier installation were performed to investigate the effect on coulombic efficiency of air-chamber microbial fuel cell. The results under three temperature stages (28-32 ºC, 16-20 ºC and 6-12 ºC) showed that coulombic efficiency can be increased by lowering operating temperature appropriately as a price for power generation loss, however, decreased seriously under excessively low temperature. The baffle-microfiltration membrane barrier trapped bacteria in the bottom part near anode, avoided the contact between bacteria and substrate in the top part with high oxygen concentration near cathode, which can decrease the loss of substrate for aerobic respiration and effectively increase coulombic efficiency from 4.5 % (control) to 9.9 %, without obvious reduction in power generation. Furthermore, the reformed reactor even showed higher performance than the control at the higher initial COD concentration range.